Modulation of the food microbiome by apple fruit processing. (December 2022) - Wicaksono, Wisnu Adi; Buko, Aisa; Kusstatscher, Peter; Sinkkonen, Aki; Laitinen, Olli H.; Virtanen, Suvi M.; Hyöty, Heikki; Cernava, Tomislav; Berg, Gabriele
Abstract: During the early life, introduction to external exposures such as consumption of solid foods contribute to the development of the gut microbiota. Among solid foods, fruit and vegetables are normally consumed during early childhood making them key components of a healthy human diet. The role of the indigenous microbiota of fruits as a source for beneficial gut microbes, especially during food processing, is largely unknown. Therefore, we investigated the apple fruit microbiota before and after processing using functional assays, advanced microscopic as well as sequencing technologies. Apple fruits carried a high absolute bacterial abundance (1.8 × 10 5 16S rRNA copies per g of apple pulp) and diversity of bacteria (Shannon diversity index = 2.5). We found that heat and mechanical treatment substantially affected the fruit's microbiota following a declining gradient of absolute bacterial abundance and bacterial diversity from shredded > boiled > pureed > preserved > dried apples. Betaproteobacteriales and Enterobacteriales were the two dominant bacterial orders (51.3%, 20.4% of the total 16S rRNA sequence reads) in the unprocessed apple. Boiling and air drying reduced the microbial load, but an unexpected, substantial fraction of 1/3 of the microbiota survived. Boiling and air drying shifted the microbiota leading to a relative increase in low abundant taxa such as Pseudomonas and Ralstonia (>2 log2 fold change), while others such as Bacillus decreased. Bacillus spp., frequently found in raw fruits, were shown to have specific traits, i.e. antagonist activity against opportunistic pathogens, biosurfactant production, and bile salt resistance indicating a probiotic potential. Our findings provide novel insights into food microbial changes during processing and demonstrate that food microbiome studies need a combined methodological approach. Food inhabiting microbes, currently considered being a risk factor for food safety, are a potential resource for the infant gut microbiome. Highlights: Bacterial diversity and bacterial absolute abundance were high in apple fruits. Bacterial isolates cultivated from apple have potential features as probiotics. Drying and boiling did not entirely eradicate the apple indigenous bacteria. Heat and mechanical treatment substantially affected the fruit's microbiota.